Chatbot basado en inteligencia artificial para soporte informativo de la Universidad Técnica Estatal de Quevedo - Mora Euvin, Luis Ignacio (2023)
The growing global demand for assistance and support in university education has driven the exploration of innovative solutions, including the use of artificial intelligence-based chatbots. These systems offer fast and effective responses, transforming the academic experience. In Ecuador, the Quevedo State Technical University faces similar challenges due to lack of 24-hour availability. The development of a chatbot accessible via WhatsApp is proposed to improve the academic experience by providing efficient responses to student queries. The project seeks to design a chatbot based on artificial intelligence that provides constant support, considering functional and non-functional requirements, ensuring ease of use, scalability and security. The development will follow an iterative and incremental approach, with evaluation based on extensive testing to measure response accuracy, response time and user satisfaction, with the aim of providing an optimal support service available at all times for university students.